Retinal single-layer analysis with optical coherence tomography (OCT) in schizophrenia spectrum disorder - T. Kregel; C. Schönfeldt-Lecuona; A. Schmidt; J. Kassubek; J. Dreyhaupt; R. Freudenmann; B. Connemann; M. Gahr; E. Pinkhardt (European Psychiatry, 2022)
Introduction